The Order of Saint Basil the Great at the End of the XVIII Century to the Year 1830 - Salamacha, Mychailas (Jaunųjų mokslininkų darbai, 2017)
The structural transformation of the Order of Saint Basil the Great in the last third of the XVIII century is investigated in the article. It is also represented the process of formation of new provinces in the Order of Saint Basil the Great. There is also shown changes in position of basilian fathers after the divisions of Rechpospolita. The text illustrates the gradual reduction of amount of the monasteries through limitation of activity of the Order of Saint Basil the Great by the governments of the Austrian and Russian empires. It is also shown the process of final liquidation of basilian monasteries in 30th of ХІХ of century in the state of Romanovi as a result of hostile politics in relation to basilians.
Keywords: The Order of Saint Basil the Great; Kapitula; Basilian Monastery; Basilian Fathers; Russian Empire